Chemogenetic Targeting of Dorsomedial Direct-pathway Striatal Projection Neurons Selectively Elicits Rotational Behavior in Mice. (1st March 2019) - Bay Kønig, Andreas; Ciriachi, Chiara; Gether, Ulrik; Rickhag, Mattias
Highlights: Chemogenetic inhibition of dorsomedial dSPNs selectively elicits ipsiversive rotations. Chemogenetic inhibition of dorsomedial dSPNs shows no effect on general locomotion. A positive linear correlation was found between turn ratio and area of viral expression. Rotational behavior is a sensitive measure of dSPN performance. Abstract: The striatum of the basal ganglia is pivotal for voluntary movements and is implicated in debilitating movement disorders such as Parkinsonism and dystonia. Striatum projects to downstream nuclei through direct (dSPN) and indirect (iSPN) pathway projection neurons thought to exert opposite effects on movement. In rodent models of striatal function, unilateral dopamine deprivation induces ipsiversive rotational behavior. The dSPNs of the dorsal striatum are believed to engage distinct motor programs but underlying mechanisms remain unclear. Here, we show by employing chemogenetics [Designer Receptors Exclusively Activated by Designer Drugs (DREADDs)] that unilateral inhibition of dorsomedial dSPNs is sufficient to selectively impair contraversive movement and elicit ipsiversive rotational behavior in mice. Adeno-associated virus (AAV) encoding Cre-dependent Gi -coupled DREADD was injected unilaterally into the dorsomedial striatum of Drd1-Cre mice, resulting in expression of the modified human M4 muscarinic receptor (hM4Di) in ∼20% of dorsostriatal dSPNs. Upon hM4Di activation, a striking positive linear correlation was found between turn ratio and viral expression, which corroborates a relationship between unilateral inhibition of dorsomedial dSPNs and rotational behavior. Bursts of ipsiversive rotations were interspersed with normal ambulation. However, partial unilateral inhibition of ∼20% of dorsostriatal dSPNs did not affect horizontal and vertical locomotion or forelimb use preference. Overall, our results substantiate a unique role of dSPNs in promoting response bias in rotational behavior and show this to be a highly sensitive measure of dSPN performance.